2011
DOI: 10.1364/ao.50.006505
|View full text |Cite
|
Sign up to set email alerts
|

Design of bent photonic crystal fiber supporting a single polarization

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. In this work, it is shown that the differential loss between the TE-and TM-polarized fundamental modes in a highly birefringent photonic crystal fiber (PCF) can be enhanced by bending the fiber. As a result, a design approach for single-mode single-polarization operation has been developed and is discussed. A rigorous full-vectorial H-field-based finite element approach, which includes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In this analysis, a Conformal Transformation [38], [39] was carried out to obtain the equivalent index of a bent PCF, and PML regions [35], [40] are introduced to absorb the leaking power. For a bent PCF, only onefold symmetry is available, and symmetry along the vertical axis is destroyed.…”
Section: Resultsmentioning
confidence: 99%
“…In this analysis, a Conformal Transformation [38], [39] was carried out to obtain the equivalent index of a bent PCF, and PML regions [35], [40] are introduced to absorb the leaking power. For a bent PCF, only onefold symmetry is available, and symmetry along the vertical axis is destroyed.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that field expands in the silica bridging region in between the air holes. We have shown that by introducing structural asymmetry easily birefrince of such fibre can be increased and it is even possible to design PCF which can only support a single polarization [17]. Although such a PCF can have a smaller spot-size to enhance supercontinuum generation, but coupling to standard SMF has remained a major obstacle for their wider application.…”
Section: Resultsmentioning
confidence: 99%
“…Birefringence is maintained by a photonic crystal pore structure. Birefringent sensors, using radiation-resistant PCFs, may be feasible for future AdvSMR temperature monitoring (Rahman et al 2011).…”
Section: Promising Research and Developmentmentioning
confidence: 99%